Influence of composition of mortar mixture on strength and deformability of external walls/Skiedinio sudėties įtaka išorinių sienos sluoksnių stiprumui ir deforma vimuisi - Marčiukaitis, Gediminas; Zabulionis, Darius (Journal of Civil Engineering and Management, 2000)
The basic element of building, wall, must satisfty not only requirements for strength, stability, but also for cracking. Experiments and practice show that in many cases external decoration layers of external walls are cracked. It is because designers and builders do not take into consideration one of the basic conditions of the theory of layers—to satisfy compatibility of deformations of layers. Therefore it is necessary to know physical and mechanical properties of plasters such as strength limits of compressive and tensile strains and modulus of elasticity. In this paper, data and recommendations about strength and deformation properties of plaster are given, as well as regressive equations by which it is possible to choose the composition of composite cement-lime-sand mortar recording the following parameters: compressive and tensile strength, limit strain, modulus of elasticity. Analysis of experimental data shows that the compressive and tensile strength of mortar and modulus of elasticity mainly depend on the ratio cement/sand. Limit deformations depend on all 3 factors: cement, lime and sand.Article in Lithuanian.First Published Online: 26 Jul 2012